ANALISIS DAYA DUKUNG PONDASI BORED PILE PROYEK PEMBANGUNAN RSNTT18-01 PASAR JUM’AT JAKARTA SELATAN - Muhammad Rizki Arif; Nur Syahidah Aini; Hadyan Arifin Bustam; Nurwanda Sari (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2025)
As urban populations grow, additional housing is urgently needed. The development of housing infrastructure is therefore crucial to supporting the community's daily activities. The Pasar Jumat High-Rise Apartment Development Project (RSNTT18-01) is located on Jalan Sapta Taruna Raya in Lebak Bulus, South Jakarta. One area worked on is the foundation. A foundation is defined as a construction at the base of a structure or building that transfers the load from the upper part of the structure or building to the soil layer below. Every foundation must be able to support loads up to a predetermined safety limit. This study aims to determine the bearing capacity of the piles that can withstand these loads. The RSNTT18-01 project uses a bored pile foundation. The bearing capacity of a bored pile foundation is calculated using bored  Penetration Test (SPT) data. According to the research, the bearing capacity of a bored pile at a depth of 12 meters is 3,8× N, with a structural load (Pu) equal to 6.5647 x 109 N, then one pile cap requires 18 piles.